PAIR vs Örmeci technique for the treatment of hydatid cyst - Örmeci, Necati (Turkish Journal of Gastroenterology, 2014)
Abstract Hydatid disease is caused by the larval stages of Echinococcus Granulosus. Most patients with hydatid disease have no symptoms, unless there is compression of vital organs such as the hepatic veins, portal vein, hepatic artery in the liver, bronchia in the lungs or the brain, resulting in life threatening complications like anaphylactic shock and sudden death. There are four treatment strategies for cystic echinococcosis (CE)- surgery, percutaneous methods,medical treatments and watch and wait strategies. Medical treatment with albendazol, mebendazole or prazyquentel may cure only 2/3 of patients with CE. More than 30% of patients will reoccur after stopping the treatment. Watch and wait strategy is followed for asymptomatic and small cysts or CE type IV and Type V cysts. Surgical treatments were the gold standard for treatment of CE until the last 30 years. Consequently, surgical methods decreased while percutaneous methods of treatment increased. Due to higher mortality, morbidity, recurrence rates, longer hospital stays and higher costs in comparison to percutaneous methods like PAIR and ÖRMECİ technique, surgical treatment must be limited for the complicated hydatid cyst. Both the PAIR and Örmeci techniques are safe and effective. However, the Örmeci technique offers a simpler, inexpensive method of treatment, with no mortality, lower morbidity, low recurrence rate, while being out patient based. It can be used as the first choice of treatment modality in patients with cysts type CE type one, CEtype two, CE Type 3A and CE Type 3B. In this review, treatment modalities for CE, but mainly percutaneous treatment, will be discussed.